2018
DOI: 10.1186/s12985-018-0979-6
|View full text |Cite
|
Sign up to set email alerts
|

Bat lung epithelial cells show greater host species-specific innate resistance than MDCK cells to human and avian influenza viruses

Abstract: BackgroundWith the recent discovery of novel H17N10 and H18N11 influenza viral RNA in bats and report on high frequency of avian H9 seroconversion in a species of free ranging bats, an important issue to address is the extent bats are susceptible to conventional avian and human influenza A viruses.MethodTo this end, three bat species (Eidolon helvum, Carollia perspicillata and Tadarida brasiliensis) of lung epithelial cells were separately infected with two avian and two human influenza viruses to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, it appears to be more likely that Egyptian fruit bats are simply not susceptible to avian H9N2 viruses coming directly from poultry without any adaptation processes. In contrast, in vitro replication studies using lung epithelial cells derived from three different bat species demonstrated a general permissiveness of these cells for other avian influenza viruses, e.g., subtype H6N1 and H2N3 [ 23 ]. On the other hand, the host species chosen to be inoculated might have been erroneous.…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears to be more likely that Egyptian fruit bats are simply not susceptible to avian H9N2 viruses coming directly from poultry without any adaptation processes. In contrast, in vitro replication studies using lung epithelial cells derived from three different bat species demonstrated a general permissiveness of these cells for other avian influenza viruses, e.g., subtype H6N1 and H2N3 [ 23 ]. On the other hand, the host species chosen to be inoculated might have been erroneous.…”
Section: Discussionmentioning
confidence: 99%
“…Animals of this species are a natural reservoir for influenza viruses of the subtype H18N11 ( 18 , 25 ). In addition, lung epithelial cells of the C. perspicillata species were shown to be permissive for avian and human influenza viruses ( 26 ). Therefore, C. perspicillata provides a good model to analyze the infection and transmission of influenza viruses from bats to other species and from other species to bats, as well as to study infection by bat influenza viruses ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…In intestines, SA α2,6-Gal receptors are more prominent in the goblet cells, lamina propria, muscularis, and serosa of the intestine [ 54 ]. The characterization of lung cell lines of bats ( Tadarida brasiliensis ) also revealed extensive SA α2,3-Gal receptors with barely detectable SA α2,6-Gal receptors ( Table 1 ) [ 55 ].…”
Section: Distribution Of Sialic Acid Receptors Among Multiple Hostmentioning
confidence: 99%